2019
DOI: 10.1186/s12891-019-2463-x
|View full text |Cite
|
Sign up to set email alerts
|

Complications after direct anterior versus Watson-Jones approach in total hip arthroplasty: results from a matched pair analysis on 1408 patients

Abstract: Background The direct anterior approach (DAA) has gained popularity in total hip arthroplasty (THA) over the past decade. A large number of studies have compared the DAA to other approaches with inclusion of a learning curve phase. The aim of this study was to compare the complication rate and bleeding between the DAA and the anterolateral approach after the learning curve phase. Methods For this retrospective, single-institutional study, propensity score matching was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…This is consistent with findings in the literature, especially in contrast to posterior approaches [33,34]. Inconsistent data exist when comparing that approach to the anterolateral one [35]. In our series, however, we were able to reach an overall complication rate comparable to the posterior approach.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with findings in the literature, especially in contrast to posterior approaches [33,34]. Inconsistent data exist when comparing that approach to the anterolateral one [35]. In our series, however, we were able to reach an overall complication rate comparable to the posterior approach.…”
Section: Discussionsupporting
confidence: 92%
“…Zhao Wang et al researched a meta-analysis about 184 cases of DAA and 175 cases of PA, demonstrated that the average incision length of DAA for THA was 3.51cm less than posterior approach [13]. Klasan et al compared DAA with anterolateral approach, demonstrated that the blood transfusion rate was statistically decreased in DAA group, with 5.8% of 14.1% lower compared to anterolateral approach [14]. Whereas, DAA could be performed in lateral decubitus position or supine position, and there were few studies conducted on comparison these two different positions of DAA for THA.…”
Section: Discussionmentioning
confidence: 99%
“…Taburculuk sırasında verilen yetersiz eğitimin hemşirenin verdiği eğitimden kaynaklandığı saptanmıştır (Tablo 7). (Higuera et el., 2011;Wright et el., 2012;Foster et al, 2015;Mclawborn et el., 2017;Deakin et al, 2018;Klasan et al, 2019). Eğitim düzenin artması bireylere verilecek olan hemşirelik eğitimin daha kolay anlaşılmasını ve uygulanmasını sağlar.…”
Section: Bulgularunclassified